Influence of Microalgae Diets on the Biological and Growth Parameters of Oithona nana (Copepoda: Cyclopoida) - Jordan I. Huanacuni; Renzo Pepe-Victoriano; María C. Lora-Vilchis; Germán E. Merino; Fressia G. Torres-Taipe; Luis A. Espinoza-Ramos (Animals, 2021)
Several species of the planktonic free-living genus Oithona have been successfully used in the larviculture of marine fish and shrimp. However, few studies have been published that allow us to estimate the potential of Oithona nana culture under controlled conditions. This work evaluated the effect of the microalgae Isochrysis galbana and Chaetoceros calcitrans as single (200,000 cells/mL) and mixed diets (100,000 + 100,000 cells/mL) on population and individual growth, ingestion rate, number of spawnings, fertility, development time by stage, and sex ratio of O. nana. We cultured this copepod at 28 ± 0.5 °C, 35 PSU salinity, 125 lux, and 12:12 photoperiod. Results showed that diet had no effect on the final population level (6273–7966 ind/L) or on individual growth, nor on sex ratio, with less males than females. With C. calcitrans, O. nana had a higher filtration rate (57 ng C/ind/day). On the other hand, a mixed diet induced a higher number of spawns (0.4 events/day) and nauplii per spawn (23 ind). Similarly, a single or mixed diet, containing I. galbana, accelerated the development rate by 6.33–7.00 days. We concluded that O. nana can be cultured with both microalgae, indicating its potential use in an intensive system for production. However, more research is required to improve the productivity of O. nana rearing.